1986
DOI: 10.1523/jneurosci.06-04-00974.1986
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of the regulation of releasable dopamine in the caudate nucleus and the nucleus accumbens of the rat brain

Abstract: In viva voltammetry has been used to measure the release of dopamine evoked by electrical stimulation of the medial forebrain bundle (MFB). Simultaneous measurements have been made with voltammetric-sensing electrodes ipsilateral to the stimulating electrode in the nucelus accumbens and the caudate nucleus of the anesthetized rat. During the stimulation, the species observed in both regions is voltammetrically identical to dopamine. Further evidence for the identity of dopamine is provided by anatomical, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
(58 reference statements)
4
43
0
Order By: Relevance
“…In vivo, electrical stimulation of the median forebrain bundle in the presence of (+ )-amphetamine resulted in an increase in the efflux of [3H]-dopamine from the caudate nucleus (Von Voigtlander & Moore, 1973). By contrast, Kuhr et al (1986) using a voltammetric technique, showed that (+)-amphetamine attenuated electrically evoked endogenous dopamine efflux in the caudate nucleus but had no effect on dopamine efflux in the nucleus accumbens. In vitro, (+ )-amphetamine either enhanced electrically evoked dopamine efflux, when measured by high performance liquid chromatography (h.p.l.c.)…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In vivo, electrical stimulation of the median forebrain bundle in the presence of (+ )-amphetamine resulted in an increase in the efflux of [3H]-dopamine from the caudate nucleus (Von Voigtlander & Moore, 1973). By contrast, Kuhr et al (1986) using a voltammetric technique, showed that (+)-amphetamine attenuated electrically evoked endogenous dopamine efflux in the caudate nucleus but had no effect on dopamine efflux in the nucleus accumbens. In vitro, (+ )-amphetamine either enhanced electrically evoked dopamine efflux, when measured by high performance liquid chromatography (h.p.l.c.)…”
Section: Introductionmentioning
confidence: 78%
“…Actions of (+ )-amphetamine on electrical stimulation during the 35 min period could not be measured. In the in vivo voltammetric study (Kuhr et al, 1986), the effect of (+ )-amphetamine on dopamine release was monitored every 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented here and in the literature suggest that the consumption of dopamine is not altered suggesting that dopamine synthesis should also be unaltered. Since the content of dopamine in the terminals mainly reflects storage pools of dopamine [19], this leaves the possibility that the amount of stored dopamine (bound to the cytoskeleton) is decreased. However, this effect should not alter dopaminergic function other than during extreme challenge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, it is commonly assumed that CPA principally measures striatal extracellular content of DA rather that of NA. Indeed, electrodes are more sensitive to DA than to NA, and the striatal DA innervation and DA tissue content are much greater than NA ones (DA:NA content is 100:1 in the caudate of mammals) (Kuhr et al, 1986;Garris et al, 1993). Striatal slices of WT and DAT-CI mice (n ϭ 6 per genotype and treatment) were superfused with 100 M amphetamine, 30 M nomifensine, or 100 M bupropion (diluted in the artificial CSF).…”
Section: Voltammetrymentioning
confidence: 99%